Terapi Musik Rebana Mampu Meningkatkan Kualitas Tidur Lansia - Luthfa, Iskim; Aspihan, Moch. (Politeknik Kesehatan Tanjungkarang, 2017)
Sleep is a basic human need that must be met. The need for sleep in the elderly ranges from 5-6 hours per day. However, changes in body condition, physical and psychological health problems cause elderly at risk of sleep disorders. Non-pharmacological interventions to overcome sleep disorders in the elderly one of them by using music rebana. The use of rebana music as a therapy is similar to occupational and physical therapy, able to stimulate the body to release epinephrine and norepinephrine that make the body relax. This relaxed condition will improve the quality of elderly sleep. The purpose of this study was to prove the use of music rebana as a therapy that can improve the quality of sleep in the elderly. This research method was quasi-experiment with the design of nonequivalent control group. The sample of this study was 56 elderly living in the Pucang Gading Seni Social Service Unit of Semarang. The sample was divided into 28 elderly intervention groups and 28 elderly control groups. Data were analyzed using Wilcoxon Signed Rank test. The result of the research showed that in the intervention group the p-value value is 0.001 (less than ᾳ 0.05) with the percentage of 65%, whereas in the control group the p-value value is 0.157 (greater than ᾳ 0.05) with the percentage of 9.99 %. In conclusion, music therapy rebana can improve the quality of sleep in the elderly with high success.